The dynamic effects of shocks to wages and prices in the United States and the euro area - Rita Duarte; Carlos Robalo Marques (European Central Bank (ECB), 2009)
This paper investigates the dynamics of aggregate wages and prices in the United States (US) and the Euro Area (EA) with a special focus on persistence of real wages, wage and price inflation. The analysis is conducted within a structural vector error-correction model, where the structural shocks are identified using the long-run properties of the theoretical model, as well as the cointegrating properties of the estimated system. Overall, in the long run, wage and price inflation emerge as more persistent in the EA than in the US in the face of import price, unemployment, or permanent productivity shocks. This finding is robust to the changes in the sample period and in the models' specifications entertained in the paper.
Keywords: C32; C51; E31; J30; 330; impulse response function; Persistence; structural error-correction model; Reallohn; Inflation; Kointegration; Zeitreihenanalyse; Makroökonometrie; Eurozone; EU-Staaten; USA